Types of dry-season stream pools: environmental drivers and fish assemblages. Issue 4 (1st October 2020) - Ilhéu, Maria; da Silva, Janine; Morais, Manuela; Matono, Paula; Bernardo, João Manuel
ABSTRACT: Many river networks in southern Europe are intermittent. In summer, the surface flow is zero and many streams become isolated pools. In this study, 128 dry season pools were studied covering first- to fourth-order streams on the Degebe River network (south Portugal). The aim of the study was to identify pool types based on environmental drivers and conditions and fish assemblages. In summer, dry streambed area exceeded 50% in all reaches and 95% in headwater sections. The pool features were primarily shaped by their location in the river network, which determined the pool morphology and the structure of fish assemblages. Pool sizes increased from upstream to downstream, as did species richness and diversity. Pools in upstream reaches were dominated by small native fishes while the larger-sized individuals tended to occupy deeper, larger, and more persistent pools. Smaller pools in downstream reaches were dominated by non-native species, which may be related to habitat preferences and minimization of negative interactions between native and non-native species. Because dry season pools represent key habitats in intermittent streams, conservation programs should be designed to reduce human pressures and improve hydromorphological heterogeneity and water quality, taking into account the natural patterns of pool types at regional and local scales.